Research review and prospects of the 2000 giant Yigong long-runout landslide: Volume, formation mechanism and recurrence period, Tibetan plateau, China - Guo, Changbao; Yuan, Hao; Wu, Ruian; Yan, Yiqiu; Yang, Zhihua (Frontiers in Earth Science, 2023)
The long-runout landslide is an unusual landslide with great drop height, long sliding distance, large volume, and high velocity, which is characterized by strong kinetic energy, fragmentation and entrainment effect. The landslide and its induced hazard chain may produce serious consequences. Based on remote sensing interpretation, field investigation and simulation, this paper summarizes the research progress of the 2000 giant Yigong long-runout landslide in Tibet, analyzes the initiating mechanism, volume and sliding velocity of the Yigong landslide, and further reveals that endogenic and exogenic geological processes are the main influencing factor of the Yigong landslide. It’s also found that the landslide has a periodic initiating mechanism with characteristics of head-cut and recurrence. However, there are great differences in the existing studies on the volume of the slide source zone in the Yigong landslide. This paper calculates the landslide volume based on ArcGIS spatial analysis and obtains an initial landslide volume of approximately 9.225×107 m3. The landslide final deposition volume is approximately 2.81~3.06×108 m3, which is consistent with the other researchers. Moreover, there are two potential dangerous rock mass in the slide source zone, with a total volume of approximately 1.86×108 m3. Dangerous rock mass may form the hazard chain of landslide-river blockage-dam break again and lead to significant disasters. Hence, we suggest the following research on Yigong landslide: stability of the potential dangerous rock mass in the slide source zone, the prediction of the hazard chain, monitoring and early warning for the landslide. It’s of great significance to guide the construction of major projects such as railway and hydropower projects and hazard prevention and mitigation in this area.